Zygomycotic Mediastinal Lymphadenitis in Beef Cattle with Ruminal Tympany - NISHIMURA, Maki (The Japanese Society of Veterinary Science, 2013)
A 9-month-old steer was autopsied due to recurrent ruminal tympany. A macroscopic examination found an enlarged caudal mediastinal lymph node, and a section of the lymph node revealed necrosis with marked calcification, similar to tuberculous lymphadenitis. Histopathologically, the lesion consisted of multiple coagulative necrotic foci and fibrosis with macrophage, lymphocyte, eosinophil and multinucleated giant cell infiltration. Non-uniform width hyphae were detected in the necrotic area and within the cytoplasm of the multinucleated giant cells, and they were found to be anti-Rhizopus arrhizus antibody positive in an immunohistochemical examination. Therefore, the steer was diagnosed with necrotic caudal mediastinal lymphadenitis due to zygomycetes infection, and inhibition of eructation by the enlarged lymph node was the likely cause of the ruminal tympany.